Genetic and immunopathological analysis of CHCHD10 in Australian amyotrophic lateral sclerosis and frontotemporal dementia and transgenic TDP-43 mice. Issue 2 (5th November 2019) - McCann, Emily P; Fifita, Jennifer A; Grima, Natalie; Galper, Jasmin; Mehta, Prachi; Freckleton, Sarah E; Zhang, Katharine Y; Henden, Lyndal; Hogan, Alison L; Chan Moi Fat, Sandrine; Wu, Sharlynn SL; Jagaraj, Cyril J; et al.
Abstract : Objective: Since the first report of CHCHD10 gene mutations in amyotrophiclateral sclerosis (ALS)/frontotemporaldementia (FTD) patients, genetic variation in CHCHD10 has been inconsistently linked to disease. A pathological assessment of the CHCHD10 protein in patient neuronal tissue also remains to be reported. We sought to characterise the genetic and pathological contribution of CHCHD10 to ALS/FTD in Australia. Methods: Whole-exome and whole-genome sequencing data from 81 familial and 635 sporadic ALS, and 108 sporadic FTD cases, were assessed for genetic variation in CHCHD10 . CHCHD10 protein expression was characterised by immunohistochemistry, immunofluorescence and western blotting in control, ALS and/or FTD postmortem tissues and further in a transgenic mouse model of TAR DNA-binding protein 43 (TDP-43) pathology. Results: No causal, novel or disease-associated variants in CHCHD10 were identified in Australian ALS and/or FTD patients. In human brain and spinal cord tissues, CHCHD10 was specifically expressed in neurons. A significant decrease in CHCHD10 protein level was observed in ALS patient spinal cord and FTD patient frontal cortex. In a TDP-43 mouse model with a regulatable nuclear localisation signal (rNLS TDP-43 mouse), CHCHD10 protein levels were unaltered at disease onset and early in disease, but were significantly decreased in cortex in mid-stage disease. Conclusions: Genetic variation in CHCHD10 is not a common cause of ALS/FTD in Australia. However, we showed that in humans, CHCHD10 may play a neuron-specific role and a loss of CHCHD10 function may be linked to ALS and/or FTD. Our data from the rNLS TDP-43 transgenic mice suggest that a decrease in CHCHD10 levels is a late event in aberrant TDP-43-induced ALS/FTD pathogenesis.